Peran Sekretaris dalam Dunia Bisnis - Zahra, Naiza Aulia (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
Secretary becomes an important role in a company, the secretary must master and understand the duties, responsibilities given by superiors. Starting from correspondence, archiving data, managing leadership schedules, as a liaison between leaders and external parties. The duties of the secretary are routine tasks, special tasks, special tasks, social tasks, data collection methods used in this study using library research, websites, and written sources both printed and electronic media, literature studies are carried out by reading literature books about secretaries, as well as books about the professionalism of secretaries, company management. A secretary must learn about the duties, functions, responsibilities and various types of secretaries in order to help superiors or leaders in a company.